SENSORY QUALITY AND CONSUMER ACCEPTABILITY OF RICE (ORYZA SATIVA L.) PUFF CHIPS AS AFFECTED BY FLAVORANTS - Villarin, Manolito D; Salinasal, Joanna Christine A; Aller, Margie C; Pascual, Pet Roey L (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Ampao is a crunchy delicacy snack made from cooked, dried and puffed rice of the City of Carcar, Cebu, Philippines and has been developed into chips with a variety of flavorants. Consumer acceptability of the product was studied using a 9-point Hedonic scale and Analysis of Variance was used to determine significant effects. These involved different flavors added to the prepared rice puff chips namely: caramel and peanut, barbeque and cheese powders. The negative and positive controls were included as treatments, the unflavored chips and the commercially available Vietnamese rice chips, respectively. The study was arranged in Randomized Complete Block Design (RCBD). Color attribute of cheese flavored rice puff chips were comparable to the commercial Vietnamese rice chips with a “like very much” rating while the caramel and peanut flavored chips were comparable to the positive control in terms of flavor and aroma having a rating of “like very much” for both sensory attributes. The barbeque flavored rice puff chips was also rated as “like moderately” and was also comparable to the positive control. The quality attributes of the rice puff chips were generally enhanced with the addition of flavorants as indicated by their mean general acceptability scores.